Proceedings of the 2012 (3rd) International Conference on Engineering, Project, and Production Management 2012
DOI: 10.32738/ceppm.201209.0027
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of External Roller Blinds Retrofit for Offices in the United Kingdom

Abstract: Fixed external shading devices, such as louvres, are widely used to combat solar gains that can lead to excessive overheating. External roller blinds, common in mainland Europe, are rarities in the UK. External roller blinds are retractable shading devices formed of horizontal slats that roll up into a casing above a window opening. They are a well developed technology with distinct advantages over fixed external shading devices. Appropriate design and applications of external roller blinds have the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Researchers have conducted LCAs for various static and dynamic insulation materials, including bio-based insulation [200,201], nano-insulation [202], PCMs [203], polyurethane [204], thermochromic materials [205], and XPS [206]. However, there is a noticeable absence of LCAs specific to topology morphing insulation, with the exception of a few studies on blinds [207,208]. This gap in the existing research presents a challenge, as without LCAs dedicated to topology morphing insulation certain potential issues, such as the impact of sun damage on materials such as polystyrene leading to higher water absorption [209], may remain undiscovered in many topology morphing insulation designs.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…Researchers have conducted LCAs for various static and dynamic insulation materials, including bio-based insulation [200,201], nano-insulation [202], PCMs [203], polyurethane [204], thermochromic materials [205], and XPS [206]. However, there is a noticeable absence of LCAs specific to topology morphing insulation, with the exception of a few studies on blinds [207,208]. This gap in the existing research presents a challenge, as without LCAs dedicated to topology morphing insulation certain potential issues, such as the impact of sun damage on materials such as polystyrene leading to higher water absorption [209], may remain undiscovered in many topology morphing insulation designs.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…According to Kunwar et al [9], the introduction of external roller shades enables an increase in energy savings, with a cooling demand decrease up to 26 %. While an in-situ study carried out by Ip et al [10] showed an annual energy demand reduction of 16 % and a maximum reduction of the air temperature of 3.5 °C when external roller shades have been implemented instead of internal venetian blinds into an office building in Brighton (U.K.).…”
Section: Introductionmentioning
confidence: 99%